Farming Areas of Madînat Ṭurṭûša (Tortosa, Catalonia): Water Wheels, Drainage, and Peasants between the Eighth and the Twelfth Centuries (Edad Media. Revista de Historia, 2019)
This article discusses the farming areas of the Muslim city of Madînat Ṭurṭûša. For this, data gathered from the written records produced after the Christian conquest (1148) have been contrasted with the findings of archaeological surveys and the analysis of the landscape morphology. The main result is the boundary fixing and plan reconstruction of three farming areas around the city. On the northern side, the huerta of Pimpí was irrigated with wells and water wheels. The Arenes plain to the south was a wetland which received periodical floods, had drainage ditches, and was mainly used for cereal land and pasture. On the opposite bank of the river Ebro, there were further drainage canals and cereal farmland, the river’s water having never been conducted through ditches to irrigate large surfaces.
Keywords: Huerta; Pasture; Drainage; Irrigation; al-Andalus